THE POTENTIAL IMPACT OF USING CHAT GPT ON EFL STUDENTS' WRITING: EFL TEACHERS' PERSPECTIVE - Rahma, Alleyza; Fithriani, Rahmah (Indonesian EFL Journal, 2024)
Chat GPT is currently gaining significant attention worldwide, including in writing. Extensive research has been conducted of writing in higher education. Many students are also utilizing Chat GPT as a new technology tool. With advances in technology, tools like Chat GPT that utilize artificial intelligence (AI) can help overcome difficulties with academic writing. However, there is known about how teachers view Chat GPT as a digital tool for English writing. The study investigates teacher perspective on using Chat GPT as a tool to support English writing, using qualitative case study approach. 10 teachers familiar with Chat participated. Questionnaires and in-depth interviews collected data on participants' viewpoints. Findings showed teachers responded positively overall to using Chat GPT to help improve students writing quality. Additionally, Chat GPT was providing useful writing features, and aiding language development. This study suggests AI technologies like Chat GPT play an important role in facilitating high-quality student academic writing.